Team Adaptation to Discontinuous Task Change: Equity and Equality as Facilitators of Individual and Collective Task Capabilities Redevelopment - Li, Alex Ning; Sherf, Elad N.; Tangirala, Subrahmaniam (Organization Science, 2023)
Teams often need to adapt to planned discontinuous task change or fundamental alteration of tasks, tools, and work systems. Although team adaptation theories have made substantive progress in explaining how teams can respond to change, they have not adequately considered the unique impact that discontinuous task change can have on teams. Such change can render not only collective but also individual task capabilities obsolete and necessitate a multilevel task relearning process. Drawing on the team compilation model, we suggest that adaptation to discontinuous task change is akin to team (re)development. We posit that teams are more effective when they approach discontinuous task change by first focusing on the rebuilding of individual task capabilities and only later shifting their attention to the rebuilding of team-level task capabilities. Moreover, we argue that the uncertainty caused by discontinuous task change makes reward fairness salient such that equity and equality in rewards are particularly useful in motivating members to (re)develop individual and collective task capabilities, respectively. We provide support for these arguments using survey, qualitative, and archival data from 115 manufacturing teams and discuss the implications of our findings for both research and practice. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2022.1621 .